PERBANDINGAN NILAI SATURATION FLOW ANTARA METODE TIME SLICE DENGAN PENDEKATAN DPU 1997. (STUDI KASUS: PERSIMPANGAN JALAN KEBO IWA DENGAN JALAN ARTERI GATOT SUBROTO BARAT) - Nyoman Widana Negara; Putu Kwintaryana; I Gede Arya Satria Bandesa Wibawa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
COMPARISON OF SATURATION FLOW VALUE BETWEEN THE TIME SLICEMETHODS WITH THE DPU (1997) APPROACH. (CASE STUDY: INTERSECTIONKEBO IWA STREET WITH WEST ARTERIAL ROAD GATOT SUBROTO)ABSTRACTSaturation flow is an important factor in the process of planning, designing and evaluating traffic lightjunctions. The purpose of this study is to find out protected saturation flow in traffic light junctions. Traffic volumedata obtained from the Automatoc Traffic Control System (ATCS) recorded, and the number of residents obtainedfrom the relevant agencies. While data such as geometric intersections, traffic signal aspects and side frictionswere survey manually. The research design used is a comparative analysis between saturation flow measurementsbased on the Time Slice method and the DPU (1997) approach. In this study applied 2 (two) treatments, namelyTreatment-1; measurement and analysis of saturation flow values based on lane width and Treatment-2;measurement and analysis of saturaton flow values based on total approach width. The results of the measurementand analysis in Treatment-1, obtained that the saturation flow value is very varied depending on the pattern oftraffic movements. In the straight lane movement (S1-1), the value of saturation flow based on the Time Slicemethod obtained at 2.130 pcu / hour is greater than 10% compared to DPU (1997) of 1.976 pcu / hour. Meanwhilein the straight lane with the right turn movement (S1.2), the saturation flow value based on the Time Slice methodof 1.681 pcu / hour is 13% smaller than DPU (1997) of 1,935 pcu / hour. Whereas, the results of measurement andanalysis at Treatment-2; the saturation flow value is relatively the same, with the value of saturation flowrespectively is based on the Time Slice method of 3.856 pcu / hour, DPU (1997) of 3,870 pcu / hour and thecombined saturation flow at Treatment-1 is 3,811 pcu / hour .